2016
DOI: 10.1002/cctc.201600723
|View full text |Cite
|
Sign up to set email alerts
|

Spin Catalysis over Conductive Solids: Enhancing the Rate of Model C−C Bond Cracking over Carbon Nanoparticles

Abstract: The concept of catalysis over a spin‐conductive mediator is investigated with quantum‐chemical calculations. Specifically, homolytic C−C bond cleavage in ethane over small edge‐oxidized half‐metallic carbon clusters in the presence of a methyl radical was considered with the complete active space self‐consistent field method. The methyl radical (spin catalyst) and carbon cluster (mediator) are found to share a common electronic orbital containing the radical unpaired electron, allowing nascent radicals emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Since the first report of spin catalysis in 1994, 21 it has been found that many spin carriers can serve as spin catalysts, which makes it possible to overcome spin conservation rules in basic chemical reactions, thus increasing the possibility of chemical reaction success. 22 , 23 , 24 There are two important mechanisms of spin catalysis: (1) Exchange (nonmagnetic) interactions of electron spins, and (2) dipole-dipole interactions of electron spins through their magnetic dipoles. 23 Carbon, being abundantly available, is a very promising candidate for constructing carbon-based materials that can act as metal-free catalysts with different electronic states and molecular structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report of spin catalysis in 1994, 21 it has been found that many spin carriers can serve as spin catalysts, which makes it possible to overcome spin conservation rules in basic chemical reactions, thus increasing the possibility of chemical reaction success. 22 , 23 , 24 There are two important mechanisms of spin catalysis: (1) Exchange (nonmagnetic) interactions of electron spins, and (2) dipole-dipole interactions of electron spins through their magnetic dipoles. 23 Carbon, being abundantly available, is a very promising candidate for constructing carbon-based materials that can act as metal-free catalysts with different electronic states and molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Stable carbon-centered neutral radicals, including open-shell graphene as a gigantic π-conjugated aromatic hydrocarbon 25 , 26 , 27 that has the spin states of a multielectron system, 28 can function as spin catalysts by allowing spin-flip processes during a reaction. 24 Here, we report the use of a free radical C(sp 2 )-C(sp 3 ) coupling reaction to synthesize two-dimensional (2D) carbon nanosheets and three-dimensional (3D) carbon organic framework (COF) nanostructures with high electron spin densities. These materials can be applied as spin catalysts in a direct imine synthesis via aerobic oxidative coupling of an alcohol (benzyl alcohol) and an amine (benzylamine or aniline).…”
Section: Introductionmentioning
confidence: 99%